2011
DOI: 10.1074/jbc.m111.287649
|View full text |Cite
|
Sign up to set email alerts
|

Heteromultimerization of Cannabinoid CB1 Receptor and Orexin OX1 Receptor Generates a Unique Complex in Which Both Protomers Are Regulated by Orexin A

Abstract: Background: Altered function has been reported when cannabinoid CB 1 and orexin OX 1 receptors are co-expressed. Results: Direct physical interactions between these receptors were observed. Conclusion:The CB 1 -OX 1 heteromer is a selective target for orexin A. Significance: Co-regulation of this heteromer may alter wakefulness and feeding behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
71
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(77 citation statements)
references
References 68 publications
5
71
0
Order By: Relevance
“…Indeed, such receptor variants (i.e. SNAP and CLIP-tagged receptors) have been utilized in the studying of CB 1 R internalization (Ward et al, 2011a(Ward et al, , 2011b). Here we used another variant, the HaloTag labeled form of CB 1 R. As indicated in our study, G protein activation and β-arrestin binding of Halo-CB 1 R have not been altered due to the N-terminal labeling, and therefore this receptor can be used to study receptor trafficking with the same advantages as the above mentioned ones.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, such receptor variants (i.e. SNAP and CLIP-tagged receptors) have been utilized in the studying of CB 1 R internalization (Ward et al, 2011a(Ward et al, , 2011b). Here we used another variant, the HaloTag labeled form of CB 1 R. As indicated in our study, G protein activation and β-arrestin binding of Halo-CB 1 R have not been altered due to the N-terminal labeling, and therefore this receptor can be used to study receptor trafficking with the same advantages as the above mentioned ones.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with a functional interaction between hypocretins and cannabinoids in reward-related processes, it has been recently shown that the intra-VTA administration of the CB 1 cannabinoid antagonist AM251 blocks the conditioned place preference induced by the chemical stimulation of LH hypocretin neurons (47). Moreover, hcrtr-1 and CB 1 cannabinoid receptors form heterodimers (48) suggesting the existence of a cross-talk between these two systems which will require future investigation.…”
Section: The Enhanced Of Dopamine Extracellular Levels In the Nucleusmentioning
confidence: 91%
“…25 In an in vitro study, it was demonstrated that the coexpression of CB1 and OX1 receptors results in a higher potentiation of ERK signalling, possibly because of heterodimerization/oligomerization of these two receptors. 26 Recently, however, it was also shown that 2-AG produced and released through the activation of OX1 receptor acts as both a paracrine and autocrine messenger via CB1 receptors, 23,27 thus possibly explaining the above-mentioned findings in the rat dorsal raphe nucleus and periaqueductal gray, as well as the potentiation of ERK phoshorylation that follows OX1/CB1 receptor coexpression. These data suggest the involvement of 2-AG and CB1 receptors not only in orexin-A release but also in orexin-mediated regulation of synaptic transmission.…”
Section: Leptin-mediated Hypothalamic Ecb/orexin Interactionsmentioning
confidence: 98%